Polyester-based particles to overcome the obstacles of mucus and biofilms in the lung for tobramycin application under static and dynamic fluidic conditions - Ernst, Julia; Klinger-Strobel, Mareike; Arnold, Kathrin; Thamm, Jana; Hartung, Anita; Pletz, Mathias W.; Makarewicz, Oliwia; Fischer, Dagmar (European Journal of Pharmaceutics and Biopharmaceutics, 2018)
Pulmonary infections with Pseudomonas aeruginosa and Burkholderia cepacia complex (Bcc) are difficult to treat and related with high mortality in some diseases like cystic fibrosis due to the recurrent formation of biofilms. The biofilm formation hinders efficient treatment with inhaled antibiotics due to a low penetration of the antibiotics through the polyanionic biofilm matrix and increased antimicrobial resistance of the biofilm-embedded bacteria. In this study, tobramycin (Tb) was encapsulated in particles based on poly(D,L,-lactide-co-glycolide) (PLGA) and poly(ethylene glycol)-co-poly(D,L,-lactide-co-glycolide) diblock (PEG-PLGA) to overcome the biofilm barrier with particle sizes of 225–231 nm (nanoparticles) and 896–902 nm (microparticles), spherical shape and negative zeta potentials. The effectiveness against biofilms of P. aeruginosa and B. cepacia was strongly enhanced by the encapsulation under fluidic experimental condition as well as under static conditions in artificial mucus. The biofilm-embedded bacteria were killed by less than 0.77 mg/l encapsulated Tb, whereas 1,000 mg/l of free Tb or the bulk mixtures of Tb and the particles were ineffective against the biofilms. Moreover, encapsulated Tb was even effective against biofilms of the intrinsically aminoglycoside-resistant B. cepacia, indicating a supportive effect of PEG and PLGA on Tb. No cytotoxicity was detected in vitro in human lung epithelial cells with any formulation.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Biofilm; Burkholderia cepacia; Cystic fibrosis; Nanoparticle; Polyester polymer; Pseudomonas aeruginosa; Tobramycin